SME’s EMPOWERMENT THROUGH INDEPENDENT FISH FEEDING DEVELOPMENT IN PLALANGAN VILLAGE SEMARANG - Iwan Hermawan; Sartono Sartono; Suharmanto Suharmanto; Gita Hindrawati; Nur Nelisa Adah (Yayasan Education and Social Center, 2023)
The COVID-19 pandemic gives an impression to the Small and Medium Enterprises (SMEs) in Semarang City. 1538 SMEs experienced losses of up to 75% and even went bankrupt. It is caused by changes in purchasing priorities from the market, so SMEs must be able to think innovatively to maintain their business. Innovation will be attached to SME products that guarantee business survival. One of them is a catfish nugget product from Atmajaya Pond. Atmajaya Pond is an SME community service program partner that can sell as many as 280 packs monthly, producing 70 kg of fish for nuggets. This figure is relatively high for a home-scale business. The raw material for nuggets is obtained from cultivation through aquaculture, which occupies a limited area beside the house. The products were distributed in Semarang and surrounding areas. Currently, the high-cost burden in the production process is feeding, so making fish feed yourself is a strategic activity to reduce production costs. SME partner now has three root problems: (1) Fails in developing fish feed products because it cannot float. (2) The products need to be more competitive because they are still modest and less eye-catching, and the packaging is not represented as iconic. (3) Processed products owned by partners cannot last long. Thus, the direction of this program will build solutions that solve these problems, such as improving fish feed production, recreating the packaging design, and adding new processed fish products. This strategic program impacts increasing skill by 89.58%, increasing knowledge by 95.83%, and strengthening production by 20%.